2013
DOI: 10.1371/journal.pone.0067501
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure Induces Telomere Instability in Human Cells

Abstract: Lead (Pb) is an important environmental contaminant due to its widespread use over many centuries. While it affects primarily every organ system of the body, the most pernicious effects of Pb are on the central nervous system leading to cognitive and behavioral modification. Despite decades of research, the mechanisms responsible for Pb toxicity remain poorly understood. Recent work has suggested that Pb exposure may have consequences on chromosomal integrity as it was shown that Pb exposure leads to the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 49 publications
4
26
0
Order By: Relevance
“…K + or Na + , in previously formed G-quadruplexes and induce formation of additional Gquadruplex structures. The authors suggested that such G-quadruplexes may persist during telomere replication which results in telomere instability and perturbations in their maintenance (Pottier et al, 2013). Similar results were reported by Liu and coworkers (2004), who studied the effects of heavy metals on hepatocytes.…”
Section: Introductionsupporting
confidence: 73%
“…K + or Na + , in previously formed G-quadruplexes and induce formation of additional Gquadruplex structures. The authors suggested that such G-quadruplexes may persist during telomere replication which results in telomere instability and perturbations in their maintenance (Pottier et al, 2013). Similar results were reported by Liu and coworkers (2004), who studied the effects of heavy metals on hepatocytes.…”
Section: Introductionsupporting
confidence: 73%
“…In in vitro studies, Pottier et al showed that Pb exposure leads to telomere instability and telomere loss due to the induction of γH2Ax foci, which are biomarkers of DNA double-strand breaks, at the end of chromosomes, near telomeres (Pottier et al, 2013). Such DNA breaks were previously reported in lead-exposed humans using the comet assay (Olewińska et al, 2010) or the micronuclei formation cytokinesis-block test (Kapka et al, 2007).…”
Section: Discussionmentioning
confidence: 91%
“…Because guanosine-rich telomeres form G-quadruplexes (Lu et al, 2013), one possible explanation for the observed shortening is the displacement of physiological ions by lead ions, which leads to more compacted G-quadruplex formation and in turn results in telomere instability and telomere maintenance impairment during replication (Pottier et al, 2013). In in vitro studies, Pottier et al showed that Pb exposure leads to telomere instability and telomere loss due to the induction of γH2Ax foci, which are biomarkers of DNA double-strand breaks, at the end of chromosomes, near telomeres (Pottier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that the DNA damage inducing the formation of γH2Ax foci resulted from a direct interaction between Pb 2+ and chromosomal DNA (Gastaldo et al, 2007). An analysis of the lead-induced γH2Ax foci revealed that they are primarily associated with the telomeric regions (Pottier et al, 2013), suggesting the presence of uncapped or shortened telomeres recognized by the protein complexes responsible for repairing DNA damage as doublestrand breaks. An increased telomere loss and doublet formation in lead-treated cells were observed due to the presence of dysfunctional telomeres, possibly resulting from defects in the replication of the lagging strand (Pottier et al, 2013).…”
Section: Maintenance Of the Telomeresmentioning
confidence: 99%